'Perceived social citizenship': a comparative study between two different hukous. Issue 2 (17th February 2019) - Jensen, Birgitte
ABSTRACT: In China, there are immense barriers to inclusive social citizenship because of the failure to overcome the institutional fragmentation of social security across the hukou division. The hukou system continues to be important in determining how social citizenship is granted in China; not only does it facilitate dual social citizenship, it imposes perceptions of deservingness that bolster these divisions. The aim of this paper is to build a social-citizenship-based framework, drawing upon the strengths of the capability approach, which is applicable to the complexity of the rural–urban divide in China. Referring to several data sources, the paper examines social citizenship as a subjective phenomenon. The paper highlights the social exclusion mechanisms embedded in the hukou system that might have an effect on social citizenship as a state of self-awareness.